2003
DOI: 10.1194/jlr.m300143-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

CD36 deficiency increases insulin sensitivity in muscle, but induces insulin resistance in the liver in mice

Abstract: CD36 (fatty acid translocase) is involved in highaffinity peripheral fatty acid uptake. Mice lacking CD36 exhibit increased plasma free fatty acid and triglyceride (TG) levels and decreased glucose levels. Studies in spontaneous hypertensive rats lacking functional CD36 link CD36 to the insulin-resistance syndrome. To clarify the relationship between CD36 and insulin sensitivity in more detail, we determined insulin-mediated whole-body and tissue-specific glucose uptake in CD36-deficient (CD36 ؊ / ؊ ) mice. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 48 publications
(64 reference statements)
9
108
0
1
Order By: Relevance
“…Under hyperinsulinemic conditions, again, CD36 KO mice showed increased whole body glucose uptake and oxidation (Goudriaan, et al, 2003). Interestingly, hepatic glucose production was not inhibited, as one would expect under these conditions (Goudriaan, et al, 2003). Analysis of tissue uptake of labeled glucose showed a significant increase in uptake in cardiac muscle in CD36 KO mice, consistent with our hypothesis that absence of fatty acid uptake by CD36 in heart leads to altered substrate utilization for energy and the fasting hypoglycemia.…”
Section: Cd36 and Insulin Resistancesupporting
confidence: 78%
See 1 more Smart Citation
“…Under hyperinsulinemic conditions, again, CD36 KO mice showed increased whole body glucose uptake and oxidation (Goudriaan, et al, 2003). Interestingly, hepatic glucose production was not inhibited, as one would expect under these conditions (Goudriaan, et al, 2003). Analysis of tissue uptake of labeled glucose showed a significant increase in uptake in cardiac muscle in CD36 KO mice, consistent with our hypothesis that absence of fatty acid uptake by CD36 in heart leads to altered substrate utilization for energy and the fasting hypoglycemia.…”
Section: Cd36 and Insulin Resistancesupporting
confidence: 78%
“…In fact, using the euglycemic clamp technique, CD36 KO mice showed slightly higher whole body glucose uptake, oxidation and lower glucose storage at basal conditions when compared with background matched wild type control mice (Goudriaan, et al, 2003). Under hyperinsulinemic conditions, again, CD36 KO mice showed increased whole body glucose uptake and oxidation (Goudriaan, et al, 2003).…”
Section: Cd36 and Insulin Resistancementioning
confidence: 98%
“…In line with these studies, it has been demonstrated that CD36 knockout mice have improved insulin sensitivity in muscle, implying that fatty acid flux into the cells plays a critical role in insulin resistance [9]. Several studies investigated the effect of various NEFAs on insulin signalling and glucose metabolism in vitro using different cell lines [10][11][12][13].…”
Section: Introductionmentioning
confidence: 91%
“…The following animals (all from Charles River Breeding Laboratories) were infected with the transgenic parasite lines: Swiss mice (male͞ female, 6 weeks old); C57BL͞6 (females, 6 weeks old); BALB͞c (female, 6 weeks old); Wistar rats (female, 11 weeks old); Spontaneous Hypertensive (SHR)͞NCrlBR rats (female, 8 weeks old) deficient in CD36 expression (14,15); Wistar-Kyoto (WKY)͞ NCrlBR rats (female, 8 weeks old) that serve as control for the SHR rats with normal CD36 expression; CD36-null C57BL͞6 (CD36 Ϫ/Ϫ ) mice (female, 8-16 weeks old) deficient in CD36 expression (16,17); wild-type control CD36 ϩ/ϩ C57BL͞6 littermates of the CD36 Ϫ/Ϫ mice (female, 8-16 weeks old); and Grammomys surdaster (male͞female, 6-12 weeks old), obtained from a breeding colony at the Institute of Tropical Medicine (Antwerp) (18). Synchronized infections of P. berghei in rodents (in vivo) and synchronized in vitro cultures were established as described in refs.…”
Section: Synchronized Blood Stage Development Of Transgenic Parasites Inmentioning
confidence: 99%